What Is Our Research For? Responsibility, Humility and the Production of Knowledge about Burundi - Devon E. A. Curtis (Africa Spectrum, 2019)
Political space in Burundi underwent a remarkable opening during the Burundian peace process and its immediate aftermath, which led to a rise in social science scholarship in Burundi. This space has increasingly narrowed, particularly since the crisis in 2015, presenting important challenges for social science scholars of Burundi. This changing political environment has consequences for the production of knowledge on Burundi. It is therefore timely to ask what purposes does research on Burundi serve. This article reflects upon different motivations and goals for social science research in Burundi and how these affect the types of research questions that are asked and the formats for knowledge dissemination. It argues that both the opening and closing of the Burundian political landscape bring into sharp relief the need for greater scholarly reflexivity. The article argues that in contexts of structural inequality and increased political control such as Burundi, we need to be particularly attentive to the need for scholarly responsibility and humility, as well as an awareness of the dynamics that have led to calls for the decolonisation of knowledge within the social sciences.